2021
DOI: 10.1088/1755-1315/765/1/012102
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic voltammetry studies of bioanode microbial fuel fells from batch culture of Geobacter sulfurreducens

Abstract: The present study aims to investigate the performance of batch culture of Geobacter sulfurreducens (G. sulfurreducens) for electrical current generation via cyclic voltammetry (CV) method. The CV study was performed with an applied voltage in the range of -0.1 to 0.1 V against the standard calomel electrode (SCE) during the cell growth and attachment of G. sulfurreducens on graphite felt and initial acetate concentration of 20 mM. The kinetics of electrode reaction was investigated by conducting CV experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…During the cathodic scan, D Na + values for peaks 4-6 are 1.22 × 10 −7 cm 2 /s, 6.27 × 10 −7 cm 2 /s and 1.71 × 10 −7 cm 2 /s, respectively. The diffusion coefficients for the anodic peaks and cathodic peaks are slightly different, which indicates that the redox process followed a quasi-reversible reaction rather than a totally reversible reaction [34].…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…During the cathodic scan, D Na + values for peaks 4-6 are 1.22 × 10 −7 cm 2 /s, 6.27 × 10 −7 cm 2 /s and 1.71 × 10 −7 cm 2 /s, respectively. The diffusion coefficients for the anodic peaks and cathodic peaks are slightly different, which indicates that the redox process followed a quasi-reversible reaction rather than a totally reversible reaction [34].…”
Section: Resultsmentioning
confidence: 95%
“…scan, DNa + values for peaks 4-6 are 1.22 × 10 −7 cm 2 /s, 6.27 × 10 −7 cm 2 /s and 1.71 × 10 −7 cm 2 /s, respectively. The diffusion coefficients for the anodic peaks and cathodic peaks are slightly different, which indicates that the redox process followed a quasi-reversible reaction rather than a totally reversible reaction [34]. Secondly, the full battery displayed in Figure 2a was further tested in a positive potential only, within the voltage range of 0~1.5 V. The scheme of the aqueous full cell is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…When B. piscis was used as the source of the adsorption processes, the adsorbed nutrients also appeared on the anodic electrode surface. These findings demonstrated that the combination of diffusion and adsorption processes limited the kinetics, demonstrating an irreversible electron charge transfer nature of these peaks [ 43 ].
Fig.7 Kinetic study of B. piscis oxidation and reduction peaks at the 5th day of inoculation at the scan rates of 5, 10, 20 mV s. −1 , a CV at different scanning rates, b , c Ip at each redox vs square root of ʋ (Randles–Sevcik equation), d , e Ep vs log ʋ (plain diamonds) and log I vs log ʋ (black triangles).
…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that a quasi-reversible electron transfer reaction occurs. 48 Plots of the square root of the scan rate versus the peak current (I p ) (Fig. 6c), showing a linear t with the R 2 = 0.999, indicate that the electron transfer on the prepared electrode surface is a diffusioncontrolled process.…”
Section: Electrochemical Behaviour Of Glucose At the Prepared Nico 2 ...mentioning
confidence: 86%